Executive compensation and corporate prestige: a systematic literature review - Dutra, Vanessa Rabelo; Silva, Wesley Vieira da; Ceretta, Paulo Sergio; Galanos, Aliki Karagrigoriou (Revista de Administração da UFSM, 2024)
Purpose: This study aims to analyze the relationship between executive compensation and corporate prestige based on scientific literature. Methodology: We systematically organized and analyzed peer-reviewed journals from 1960 to 2021 to assess the academic progression in executive compensation and corporate prestige. We analyzed 59 articles from the Web of Science Core Collection and Scopus databases. Findings: We identified an increase in the rate of publications per year on this topic. The synthesis of the literature reveals that, fundamentally, the United States carried out the studies. Results also show that there is little relationship between researchers, and, finally, we identified a gap in the literature as most studies on executive compensation do not consider corporate prestige, performance, and compensation together. Originality/Value: This study is a pioneer in undertaking a systematic literature review considering the interconnection between compensation and prestige. The contributions of this study consist of identifying and systematizing knowledge and deriving the research gap and future research, which is helpful for academics and practitioners to understand executive compensation and corporate prestige as the data reveal a field of study to be considered and analyzed.